The Conundrum of Collaboration: Examining Collaboration as a Continuum Towards Professional Learning - Burnside, Scott Harold Tavares (Scholarship@Western, 2021)
Stories are a collaborative effort between teller and listener; utilizing the First Nations Métis Inuit (FNMI) tradition of Storytelling, this organizational improvement plan recounts the story of teacher collaboration at Ginkendan Secondary School (GSS, a pseudonym). A systems theory lens will be employed to frame a problem of contrived collegiality, a state of perfunctory collaboration resulting from dictated professional development that does not lead to professional learning. A feedback loop of teacher-derived professional learning will be investigated to propel teachers forward on a conceptual framework of a collaboration continuum. Comfortable collaboration, a stage where teachers are empowered to address their own problems of practice, will mark a new stage on the continuum. This stage is differentiated through professional learning circles/communities. Teacher Leaders will orient teachers to new professional learning and empower others towards a more critical state. A final stage of collaboration, critical colleagueship, will be investigated through a mentor-like relationship. This stage is marked by a 4C framework and is the most difficult, as it involves close scrutiny by other teachers, opening the classroom doors to new ideas, and growing new learnings. Finally, the FNMI moral teaching of the Medicine Wheel will communicate a plan for change that can support teachers in different stages of their growth and practice.